Biocatalyst-mediated selective acylation and deacylation chemistry on the secondary hydroxyl/amine groups of nucleosides. (2nd December 2021) - Khan, Amarendra Mohan; Agnihotri, Narinder Kumar; Singh, Vinay Kumar; Mohapatra, Subash Chandra; Mathur, Divya; Kumar, Manish; Kumar, Rajesh
Abstract: Nucleosides play a pivotal role in biological systems and therefore have attracted a lot of interest as chemotherapeutic agents in drug discovery. Over the years biocatalysts have emerged as a sustainable alternative to conventional synthetic catalysts. As a nature's catalyst, they exhibit excellent selectivity, remarkable tolerance, and help in carrying out eco-friendly benign processes. The use of a biocatalyst as a regio- and enantioselective catalyst is particularly relevant in the transformations of nucleosides and their analogs because of the presence of multiple chiral centres. Herein, we discuss the recent advances in the Pseudomonas Cepacia Lipase mediated selective acylation and deacylation reactions of the secondary hydroxyl and amino groups of nucleosides and their analogs.